2015
DOI: 10.1002/hep.27969
|View full text |Cite
|
Sign up to set email alerts
|

World‐wide relative contribution of hepatitis B and C viruses in hepatocellular carcinoma

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) are major causes of hepatocellular carcinoma (HCC). In order to assess the relative contribution of HBV and HCV to HCC worldwide, and identify changes over time, we conducted a systematic review of case series published up to the year 2014. Eligible studies had to report seroprevalence of both hepatitis B surface antigen (HBsAg) and antibodies to HCV (anti‐HCV), alone and in combination, for at least 20 adult HCC cases. Studies using a first‐generation enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
346
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(358 citation statements)
references
References 33 publications
10
346
1
1
Order By: Relevance
“…Patients who received sorafenib and HAIC, and for whom frozen serum was available, were not artificially enrolled in this study. However, the frequency of patients with HBV was higher than the usual case for HCC patients in Japan [42,43].…”
Section: Patients Treated With Haic Treatmentmentioning
confidence: 69%
“…Patients who received sorafenib and HAIC, and for whom frozen serum was available, were not artificially enrolled in this study. However, the frequency of patients with HBV was higher than the usual case for HCC patients in Japan [42,43].…”
Section: Patients Treated With Haic Treatmentmentioning
confidence: 69%
“…Liver cancer cases mostly occur in Africa and Asia, where the high number of hepatitis B and hepatitis C cases strongly predisposes to the development of liver disease and the subsequent development of liver cancer (6,7). Consequently, comprehensive elucidation of the mechanisms governing recurrence of liver cancer and metastasis are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from a systematic review of HCC case series has also shown younger ages at diagnosis of HBVrelated HCC in sub-Saharan Africa than in Asia. 2 Drawing such conclusions from case series is questionable, because the median age at HCC diagnosis can be strongly affected by the underlying population's age distribution. Indeed, the median age of the population in sub-Saharan Africa is lower than in Egypt (18 vs 25 years), 3 reflecting the higher risks for competing causes of death in sub-Saharan Africa.…”
Section: Main Textmentioning
confidence: 99%